Blue phases decorated with colloidal particles: photonic crystals - Ravnik, Miha; Zumer, Slobodan (Photonics Letters of Poland, 2011)
The recent efforts to understand self-assembly of ’soft’ photonic colloidal crystals in intrinsic disclination networks of body centered and face centered cubic lattices of blue phases I and II are briefly reviewed. Full text: PDF References: S. Wong, V. Kitaev, G.A. Ozin, "Colloidal Crystal Films: Advances in Universality and Perfection", J. Am. Chem. Soc. 125, 15589 (2003). [CrossRef] D.C. Wright, N.D. Mermin, "Crystalline liquids: the blue phases", Rev. Mod. Phys. 61, 385 (1989). [CrossRef] W. Cao, A. Munoz, P. Palffy-Muhoray, and B. Taheri, "Lasing in a three-dimensional photonic crystal of the liquid crystal blue phase II", Nature Mater. 1, 111 (2002). [CrossRef] Y. Hisakado, H. Kikuchi, T. Nagamura, T. Kajiyama, "Large Electro-optic Kerr Effect in Polymer-Stabilized Liquid-Crystalline Blue Phases", Adv. Mater. 17, 96 (2005). [CrossRef] H. Kikuchi, M. Yokota, Y. Hisakado, H. Yang, T. Kajiyama, "Polymer-stabilized liquid crystal blue phases", Nature Mater. 1, 64 (2002). [CrossRef] H.J. Coles, M.N. Pivnenko, "Liquid crystal ’blue phases’ with a wide temperature range", Nature 436, 997 (2005). [CrossRef] F. Castles, S.M. Morris, E.M. Terentjev, H.J. Coles, "Thermodynamically Stable Blue Phases", Phys. Rev. Lett 104, 157801 (2010). [CrossRef] M. Ravnik, G.P. Alexander, J.M. Yeomans, S. Zumer, "Mesoscopic modelling of colloids in chiral nematics", Faraday Discuss. 144, 159 (2010). [CrossRef] S. Zumer, M. Ravnik, T. Porenta, G.P. Alexander, J.M. Yeomans, "Blue phases as templates for 3D colloidal photonic crystals", Proc. SPIE 7775, 77750H (2010). [CrossRef] M. Ravnik, G.P. Alexander, J.M. Yeomans, S. Zumer, "Three-dimensional colloidal crystals in liquid crystalline blue phases", PNAS Early Edition, February 28, (2011). [CrossRef] M. Skarabot, M. Ravnik, S. Zumer, U. Tkalec, I. Poberaj, D. Babic, I. Musevic, "Hierarchical self-assembly of nematic colloidal superstructures", Phys. Rev. E 77, 061706 (2008). [CrossRef] M. Ravnik, S. Zumer, "Landau-de Gennes modelling of nematic liquid crystal colloids", Liq. Cryst. 36, 1201 (2009). [CrossRef]